Contribution of Middle-Income Economies in Literature Pertaining to Customer Loyalty : A Critical Appraisal - Gulati, Twinkle; Shankar, Siddharatha (Indian Journal of Marketing, 2023)
Purpose : A retrospective investigation was carried out to critically appraise the research inputs of middle-income economies in the extant literature on the theme of customer loyalty in the marketing domain. Methodology : This review article objectively, systematically, rigorously, and critically appraised the knowledge paradigms that existed in 495 documents extracted using the Scopus database. The breadth and depth of the past literature were examined through bibliometric analysis by structuring the diverse research constituents using the Bibliometrix R package and VOSviewer. Findings : The results logically exhibited the publication trend and citation structure, country collaboration pattern, keyword co-occurrence analysis, co-citation of references analysis, and many other descriptive bibliometric indicators, including leading journals, prolific authors, and influential documents. Practical Implications : The study functions as a stimulus that contributes significantly to theory and practice by offering a globally inclusive research outlook for the said theme and an idiosyncratic assessment to practitioners in emerging markets. Originality : Besides serving to elucidate, map, and visualize the stated research premise, this first kind of bibliometric review through the lens of middle-income economies on customer loyalty strengthens the value in terms of subject-matter quantification.